Strategi Pengembangan Pemasaran dan Manajemen Usaha Wisata Towilfiets - Authentic Jawanese Village Cycling Tour di Kulonprogo Yogyakarta - W, Widarta; Slamet, Agus; Panglipursari, Diw Lesno (Yayasan Daarul Huda Kruengmane, 2024)
Towilfiets - Authentic Javanese Village Cycling Tour is a typical antique cycling tour concept with a trip around villages and rice fields in Bantar Kulon Village, Sentolo, Kulon Progo. Tourists can feel and be directly involved with the lives of residents. Towilfiets offers visitors in addition to seeing the rural environment, including the historic bridge made by Ir Soekarno, namely the Bantar bridge, which connects Sleman Regency and Kulon Progo Regency which was built during the Dutch aggression. PKM aims to optimize marketing through social media. By realizing the great potential as a marketing medium, they create interesting and informative content that can attract the attention of potential tourists. One of the increasing number of followers and impressions on Towilfiets' TikTok account reflects the effectiveness of this move. The marketing strategy that we carry out in the form of marketing digitalization, branding, management, and web development is expected to become a leading tourist destination that can attract tourists. One of the strategic steps of website development specifically for Towilfiets. By creating a digital platform www.towilfiets.com, they provide access to information to prospective tourists about onthel bicycle tour tour packages, as well as other details that support the attraction of Towilfiets. The use of this technology is an indicator of success in achieving public awareness of these tourist destinations.